Evaluation of Ventilator Associated Respiratory Tract Infections (VARTI) by Common Anaerobic and Atypical Bacteria among the Patients of ICU of a Tertiary Care Hospital in Bangladesh - Alam, S K Saiful; Mohammad, Taneem; Chowdhury, Moinul Hassan; Naser, Mohammad Jamal Abdel; Ashrafuzzaman, Mohammad; Shamsuzzaman, S M (Journal of the Bangladesh Society of Anaesthesiologists, 2021)
Background and aim of the study:Ventilator-associated respiratory tract infection (VARTI)is theleading cause of higher mortalityand morbidity in ICU compared to non-ICU patients. Thisarticlereveals etiology of VARTI by commonanaerobic and atypical bacteria in ICU of Dhaka Medical College. Materials and Methodology: This is a cross-sectionalstudy where 200 endotracheal aspirate (ETA)samples were taken from clinically suspected patients of VARTI. After proper screening,bacteria were identified by PCR as because anaerobic and atypical bacteria cannot be easily grown inconventional culture media. Result: Sixty three (31.5%) samples were found to have VARTI. Among the common atypicalbacteriacausing, M. pneumoniae was found in 4 (6.35%) and L. pneumophila in 2 (3.17%) of the 63 samples. Insearch of the anaerobic bacteria causing VARTI,Peptostreptococcus was detected in 3 (4.76%) whileFusobacterium nucleatum andPrevotella melaninogenicawere detected in 2 (3.17%) each of the 63 samples. Conclusion: Anaerobic and atypical bacteria are implicated in VARTI in ICU although at a relative lowrate. JBSA 2021; 34(1): 32-37